Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.9734/acri/2019/v19i230153
|View full text |Cite
|
Sign up to set email alerts
|

Health Risk Assessment of Heavy Metal Intake of Common Fishes Available in the Brahmaputra River of Bangladesh

Abstract: Fifteen (15) fish species were collected from three (3) locations of the Brahmaputra River to determine heavy metals content in fish flesh, and to assess potential human health risk through consumption of those fishes. The contents of heavy metals in aqueous extract of different fish species were determined by an atomic absorption spectrophotometer (AAS) at the Department of Agricultural Chemistry, Bangladesh Agricultural University, during the period from March to June, 2018. The concentrations of Mn, Zn, Cu,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Such metallic contamination comprises significant portion of the problem as these metals known for their bioaccumulation and biomagnification, which cause various health hazards to human. Polluted fish could be a dangerous dietary source of certain toxic heavy metals to human [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such metallic contamination comprises significant portion of the problem as these metals known for their bioaccumulation and biomagnification, which cause various health hazards to human. Polluted fish could be a dangerous dietary source of certain toxic heavy metals to human [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Essential metals include Fe, Cu, Zn and Mn, whereas nonessential metals are Hg, Pb, Ni and Cd [6]. Evidently, fish form the link for the transfer of toxic heavy metals from water to humans [4]. A number of serious health problems can develop as a result of excessive uptake of different metals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MPI can be included in complex freshwater monitoring programs as it can produce some additional information about metal bioavailability, bio-concentration, and metal penetration into the environment. The MPI is a reliable and sensitive method for monitoring metal contamination in food samples (Zakir et al 2019). In this study, the MPI value in LV was found to be slightly higher than the MPI value in LK.…”
Section: The Degree Of Metal Contaminationmentioning
confidence: 58%
“…But near Loja City, it is advisable to make a holistic environmental assessment to estimate the environment's health [35]. This research can also be used as an environmental baseline for future mining projects in the sector.…”
Section: Discussionmentioning
confidence: 99%